2022
DOI: 10.1111/os.13521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Home‐Based Telerehabilitation Program for Geriatric Hip Fracture Following Total Hip Replacement

Abstract: Objective To compare the effectiveness of a six‐month home‐based telerehabilitation based on the Internet‐based rehabilitation management system coupled with conventional outpatient care in elderly patients with hip fractures following total hip replacement (THR). Methods Elderly patients (aged over 65 years) with first hip fractures who underwent THR between March 2018 and September 2018 in Tianjin Hospital were enrolled in this study. Patients were divided into two groups: telerehabilitation group (n = 43) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…They confirmed the improvement of functional recovery of hip fractures thus enhancing the ability to perform activities of daily living and somatic integration by the Internet-based rehabilitation management system applied to postoperative home rehabilitation of hip fractures [15]. Another study comparing the efficacy of telephone and telerehabilitation groups is by Wu et al [16]. In Wu`s study "Familyoriented postoperative rehabilitation management system for geriatric hip fracture includes video communication, application and working portal of doctors" was used as a telerehabilitation method [16].…”
Section: Efficacy Of Telerehabilitation After Hip Fracturementioning
confidence: 78%
See 3 more Smart Citations
“…They confirmed the improvement of functional recovery of hip fractures thus enhancing the ability to perform activities of daily living and somatic integration by the Internet-based rehabilitation management system applied to postoperative home rehabilitation of hip fractures [15]. Another study comparing the efficacy of telephone and telerehabilitation groups is by Wu et al [16]. In Wu`s study "Familyoriented postoperative rehabilitation management system for geriatric hip fracture includes video communication, application and working portal of doctors" was used as a telerehabilitation method [16].…”
Section: Efficacy Of Telerehabilitation After Hip Fracturementioning
confidence: 78%
“…Also, @ctivehip telerehabilitation is used in another study and showed better results compared to the home-in-person rehabilitation [20]. More Interactive rehabilitation setting with microcontrollers to check patient's fever, blood pressure, glucose level, and blood oxygen levels was used in a study showing improvement of the physical rehabilitation of patients and also play a positive role in psychological rehabilitation and the prevention of complications compared to group delivering rehabilitation by phone [16]. The same telerehabilitation system with microcontrollers is used in Zhang`s study compared to telephone rehabilitation and same conclusion with improving in the functional recovery of the hip joint and enhancing perform of the daily activities [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, telerehabilitation appears to be particularly beneficial to elderly patients with hip fractures. 42 …”
Section: Discussionmentioning
confidence: 99%